Integrating Religious Values and Modern Quality Standards: A Multi-Site Inquiry into SDG 4 Achievement in Pesantren-Based Schools - Matnasir Matnasir; Sujarwanto Sujarwanto; Nunuk Hariyati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study aims to analyze and describe: (1) quality planning; (2) quality control; (3) quality improvement; (4) supporting factors; and (5) inhibiting factors in the implementation of quality management in pesantren-based schools. Method: The study employed a qualitative approach using a multi-site case study design. Data were collected through in-depth interviews, observations, and documentation involving principals, vice principals, teachers, educational staff, students, and parents. Data analysis was conducted through data condensation, data display, conclusion drawing and verification, single-site analysis, and cross-site analysis. Data trustworthiness was ensured through source triangulation, technique triangulation, theory triangulation, member checking, and audit trails. Results: The findings revealed that: (1) quality planning was carried out through stakeholder needs identification, the development of programs and an integrated curriculum, and the strengthening of pesantren values in educational quality planning; (2) quality control was implemented through instructional supervision, discipline monitoring, program evaluation, academic achievement evaluation, and the development of students’ religious character; (3) quality improvement was achieved through human resource development, instructional innovation, educational technology enhancement, infrastructure development, and a culture of continuous improvement; (4) supporting factors included visionary leadership, pesantren culture, human resource competence, stakeholder support, and commitment to quality; and (5) inhibiting factors included rapid technological changes in education, the need for continuous human resource development, the complexity of managing both school and pesantren programs, and the challenge of balancing educational modernization with pesantren traditions. Novelty: The novelty of this study lies in the development of a quality management model for pesantren-based schools that positions pesantren culture as the foundation for the formation of a quality culture. This quality culture strengthens the implementation of quality planning, quality control, and quality improvement based on Juran’s Trilogy, thereby producing educational quality that is academically excellent, religiously grounded, and globally competitive for SDG 4.